The role of CD83 in the pathogenesis of immune thrombocytopenia - Xiuli Wang; Qiyuan Zhou; Wen Yang; Hui Bi; Honghui Wang; Yacan Wang; Yadong Du; Lin Liu; Yuebo Liu; Liefen Yin; Jin Yao; Jingxing Yu; et al. (Hematology)
Background CD83 are closely related to the pathogenesis of immune thrombocytopenia (ITP), but the exact mechanism remains unclear.Aim To explore the relationship between CD83 and CD4+ T cell subsets and clarify the role of CD83 in the pathogenesis of ITP.Methods RT-qPCR and Flow cytometry were used to illustrate CD83 expression. The downregulation and overexpression of DC-CD83 were co-cultured with CD4+ T cells to detect cell proliferation, co-cultured supernatant cytokines and Tregs expression.Results The results indicate that the ITP patients showed higher expression of CD83 than the healthy controls. The proliferation of CD4+ T cells was inhibited by downregulation of DCs-CD83 but promoted by overexpression of DCs-CD83. siRNA-CD83 inhibited proinflammatory IFN-γ and IL-17 secretion while raising TGF-β, IL-10 concentrations. Overexpression of DCs-CD83 promoted Tregs expression.Conclusion The Th1/Th2 and Th17/Tregs polarization were reversed via interfering DCs with siRNA-CD83. CD83 plays an important role in ITP pathogenesis, suggesting novel treatment for ITP patients.